Culturally Responsive Teaching (CRT) on Thermochemistry with AR: Action Research - Aji, Eko Trian Pramono; Ardyansyah, Ananta; Nareswari, Tsalis Jauza; Sa’diyah, Noviachri Imro’atul; Rahmawati, Ulfa (IJCER (International Journal of Chemistry Education Research), 2025)
Mastering thermochemistry can be challenging for students. This study tackles teaching thermochemistry, a challenging subject with complex concepts, calculations, and lab work that students often struggle with. A structured learning approach integrating Culturally Responsive Teaching (CRT) with Augmented Reality (AR) was implemented. Conducted through action research over two cycles, the study involved 35 high school students during the 2023/2024 academic year. The study found significant improvements, with average scores rising from 76.74 in Cycle I to 83.94 in Cycle II, and the percentage of students achieving classical completion increasing from 65% to 77%.